Competitiveness of basics industries Ukraine and ways of protection of national interests in the WTO - Белевская, Ольга Александровна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
In the article the author's three-level conceptual model of state support to improve the competitiveness of basic industries of Ukraine in the global world after joining the WTO. Author used the results of leading Ukrainian and foreign scientists in the research topic. They include quantitative analysis of changes in the development of automobile industry and Ukraine's place among some countries in terms of commitments in 2013 fo the countries of the WTO bound rates of import duties.